Public Administration of Social Security in the Republic of Kazakhstan - KARAYEV, Alipasha Agahanovich; MUKHTAROVA, Aizhan; TILEUBERGENOV, Yerazak Manapovich; KASSYMBEK, Aliya; KHAMZINA, Zhanna Amangeldinovna (Journal of Advanced Research in Law and Economics, 2016)
Formation of social statehood in Kazakhstan requires a lot of work in the form of state control mechanisms aimed at creating conditions for a dignified human life. 25 years of development of Kazakhstan as an independent state did not ensure the formation of social laws that would fully guarantee the realization of the social rights of the individual in accordance with recognized standards. Development of socially organized state in Kazakhstan requires active work of the public sector on the formation of high-quality social protection system. The article examines the state-legal basis of social welfare in the Republic of Kazakhstan, problems of formation of the Republic of Kazakhstan in social legislation and social standards. The aim of the investigation is a comprehensive study of the problems of legal regulation of the state management in the sphere of social protection with the development of concrete proposals to improve the regulatory framework of Kazakhstan in relation to the creation of conditions for the realization of social rights of the individual. The methodological basis of the research is grounded on the principles of knowledge of social and legal phenomena in the area (including ideas, concepts and theories) in their historical development, interconnection and interdependence of the theoretical and applied; general scientific approaches – systematic, integrated, personal and social-activity, historical and legal, comparative legal, social and economic; empirical methods – survey, study and generalization of experience, reviews and reports on the activities of the social services in the Republic of Kazakhstan and its territorial bodies, materials of state statistical observation. As a result of the analysis the problematic issues of governance of social protection system in the Republic of Kazakhstan were examined; state-legal mechanism of regulation of social protection of the population was studied; the problems of formation and development of norms of social rights, taking into account national peculiarities of the Republic of Kazakhstan, were identified; it was studied the mechanism of implementing the principle of assurance of social security; the features of legal regulation of social protection standards. The results can be used in the development of national legislation in the field of social security, in the form of measures to improve governance mechanisms in this area. They may be useful for the public authorities in the implementation of work while providing of social standards.
Keywords: governance; social protection; social standards